تأملات في علم اللغة العربية وتعليمها في القرن 21: (Teaching Arabic language in the 21st Century: Problems, Challenges and Suggestions) - محمد أكرم سعد الدين, (At-Tajdid - Intellectual Refereed Journal, 2022)
-